Pengaruh Stres Kerja, Beban Kerja dan Lingkungan Kerja Terhadap Turnover Intention Karyawan CV. Mitra Sahabat Grup Kabupaten Pesawaran - Yateno; Nina Lelawati; Angga Wahyudi (Jurnal Manajemen DIVERSIFIKASI, 2025)
Turnover intention is an employee's desire to resign from work with the aim of looking for anew job based on their abilities and a feeling of dissatisfaction with work achievements sofar, therefore there is a turnover of employees in a company without any coercion fromoutside parties or, hence the cause employee turnover due to factors that influence it. Thisresearch aims to find out whether work stress has a direct effect on turnover intention. Tofind out whether workload has a direct effect on turnover intention. To find out whether thework environment has a direct effect on turnover intention. The sample for this research is allemployees at CV. Mitra Sahabat Grup totaling 45 people. Data collection usesquestionnaires and literature studies, and data analysis uses validity tests, reliability tests,normality tests, linearity tests, homogeneity tests, multiple regression analysis, T tests, Ftests, and coefficient of determination (R2) tests using the program (SPSS) . The researchresults show that there is a positive and significant influence of Job Stress on TurnoverIntention. There is a positive and significant influence of Workload on Turnover Intention.There is a positive and significant influence of the work environment on turnover intention